A debilidade mental como solução estabilizadora de uma psicose - Aline Cristina Rosa (2011)
The mental handicap, since the beginning of its theorizing, in the field of psychiatry and psychology, was linked of unalterably way to the weakness, to insufficient, to the deficit of mental faculties, mainly about cognitive functions. Its cause, since the beginning, was referred to organic, and the diagnosis, from the emergence of psychometrics, has been based on intelligence tests so far, under the imperative from a differential psychology. The mental handicap remains nowadays, solidarity-in the field of psychiatry, from psychology and pedagogy about the IQ. Psychoanalysis, in turn, comprehends the mental handicap not like a disorder of intelligence, but like a subjective position adopted by the subject of the unconscious. In psychoanalytic conception, the mental handicap refers to a person who was subjected to the demand from the Other, who does not appropriate about his/her words and not so far from his/her desire. Through a construction of a clinic case we try to elucidate the stabilization of a psychosis through this subjective positioning from the subject: the debility, which was initially presents itself as a symptom to be treated, has been configured as the treatment itself from the jouissance which invaded the patient. The behavior analyst, therefore, reorients himself/herself from the solution that the subject builds compared to the effects of psychosis.